Bioenergy generation and simultaneous nitrate and phosphorus removal in a pyrite-based constructed wetland-microbial fuel cell. (January 2020) - Ge, Xiaoyan; Cao, Xin; Song, Xinshan; Wang, Yuhui; Si, Zhihao; Zhao, Yufeng; Wang, Wenting; Tesfahunegn, Awet Arefe
Graphical abstract: Highlights: The PCW-MFC enhanced simultaneous nitrate and phosphorus removal. The PCW-MFC generated much more bioelectricity than the CW-MFC. A stable pH value and low sulfate concentration were observed in the PCW-MFC. Geobacter and sulfate-reducing bacteria (SRB) were enriched in the PCW-MFC. Abstract: This study investigates the performance of a pyrite-based constructed wetland-microbial fuel cell (PCW-MFC) in chemical oxygen demand (COD), nitrate (NO3 − -N), total inorganic nitrogen (TIN), and total phosphorus (TP) removal and bioelectricity generation, and explores the mechanisms involved. Four microcosms were used: a constructed wetland (CW), a pyrite-based constructed wetland (PCW), a constructed wetland-microbial fuel cell (CW-MFC), and a PCW-MFC. After 180 days' operation, the PCW-MFC exhibited enhanced simultaneous nitrate and phosphorus removal and bioelectricity output. The maximum COD, NO3 − -N, TIN, and TP removal efficiencies in the PCW-MFC were 71.9%, 70.1%, 63.2%, and 91.2%, respectively, for a hydraulic retention time (HRT) of 6 h. The mean bioelectricity output of the PCW-MFC was 19.0–28.4% higher than that of the CW-MFC. The nitrate removal rate constant of the PCW-MFC was 1.04 d −1, which is significantly higher than those of the others. Geobacter and sulfate-reducing bacteria were enriched in the PCW-MFC.